Advanced Treatment of Fission Yield Effects and Method Development for Improved Reactor Depletion Calculations - Kern, Kilian (KIT Scientific Publishing, 2019)
Fission product yield data play an important role in simulations of nuclear fission reactors, aimed at fuel cycle and safety analyses. The respective evaluated data libraries still have shortcomings regarding the treatment of energy dependencies and uncertainty information. This work has been aimed at the development of a fission model for future fission product yield evaluations as well as its validation on the levels of cross-sections, fission product yields and time dependent decay radiation.